Reintroduction of nitrofurantoin in the treatment of uncomplicated urinary tract infection (Bangladesh Journal of Pharmacology, 2021)
The present study was designed to reintroduce an older antimicrobial nitrofurantoin among a group of prescribers and to explore the relationship between the reintroduction and corresponding shift in sensitivity pattern of the microbes. The microbial sensitivity against ciprofloxacin before intervention was 46.6%, which significantly increased after intervention (51.8%). Treatment with nitrofurantoin resulted in a total clinical cure rate of 80.6%, of which rate of clinical cure achieved in expected time was 66.1% and delayed was 14.5%. The rate of total clinical cure with nitrofurantoin corresponded closely with the proportion of urinary isolates sensitive to nitrofurantoin. i.e., 86.3%. This preliminary study revealed that revival might be an effective strategy to increase the sensitivity and to delay the emergence of resistance.